Validation of the French version of the Body Awareness Questionnaire: toward a way to assess alexisomia - Carre, Arnaud; Shankland, Rebecca; Guillaume, Philippe; Duclos, Jeanne; El-Jor, Claire; Pellissier, Sonia; Flaudias, Valentin (Frontiers in Psychology, 2024)
First, I would like to thank the authors for the work they have done. In their study they investigated alexithymia and alexisomia, both trying to prove association between these concepts and to conduct a validation in the French language. Both concepts are of high importance and interest in understanding somatic and mental disorders. However, the manuscript lacks a clear structure, which might be caused by presenting too many information by reporting the validation study and the association between alexithymia and alexisomia at the same time.A more precise title and structure in writing will be useful to guide the reader through both study aims in a more easy way. Also I suggest to shorten the manuscript, overall the introduction and discussion, and to concentrate on the relevant content.Answer : We sincerely thank the reviewer for this comment. We have reduced the introduction and discussion and tried to refocus on two more identifiable axes: an axis on the validation of the scale, and an axis on the link between alexithymia and alexisomia.